Conditional Handicaps in Exuberant Lizards: Bright Color in Aggressive Males Is Correlated with High Levels of Free Radicals - Friesen, Christopher R.; Wilson, Mark R.; Rollings, Nicky; Sudyka, Joanna; Whittington, Camilla M.; Giraudeau, Mathieu; Olsson, Mats (Frontiers in Ecology and Evolution, 2017)
Two non-independent theories in evolutionary ecology, the immunocompetence and the oxidative handicap hypotheses, may explain maintenance of genetic variation and signal honesty through genic capture in sexual selection biology. Thus, polygenic traits, like body condition, could help maintain variation in signalling traits under strong, directional sexual selection while maintaining signal honesty. The immunocompetence and oxidative handicap hypotheses are complementary in this regard in that hormones (most often steroids) essential for sexual signalling also carry costs, including increases in potentially damaging reactive oxygen species (ROS). Here we combine (at least) two of these hypotheses in a study of morph-specific condition and free radical effects on signalling traits (head coloration) in males of a polymorphic lizard, the Australian painted dragon (Ctenophorus pictus). Males differ in head colour (red, orange, yellow, hereto forth collectively ‘yellow-reds’), with these morphs showing reproductive tactics and behaviour in a graded fashion of aggression and dominance (red highest levels). A blue morph recently emerged in our study population and has never been behaviourally characterised. Body condition varied significantly in its relationship with superoxide among the four morphs, with males in better condition showing higher superoxide levels in ‘yellow-reds’ (least so in red males). Blue males contrasted markedly by showing lower superoxide levels in males in better condition, perhaps facilitated by no (or reduced) dermal deposition of pigmentation. Colour degradation with loss in condition from yellow to red males, suggesting that red males (i.e., genes associated within a more aggressive morph) is more able to maintain colour with superoxide acting as a potential handicap. This result is consistent with handicap principles in that males with the more pronounced signal carry a higher cost (higher ROS levels) when being in better body condition, while maintaining more vivid coloration (the condition-dependent trait).